STRATEGI PEMBERDAYAAN EKONOMI KREATIF DALAM MENIGKATKAN PENDAPATAN MASYARAKAT DESA LAMOIKO KECAMATAN TANGGETADA - Kasmiah Kasmiah; Rahmi Rahmi S (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
This study aims to find out how the strategy of empowering the creative economy in increasing the income of Lamoiko villagers. The formulation of the problem in this research is how is the creative economy empowerment strategy in increasing the income of the community in Lamoiko Village, Tanggettada District ?. The purpose of this study is to describe the strategy of empowering the creative economy in increasing community income in the Lamoiko Village, Tanggetada District. The results of this study indicate that the creative economic empowerment strategy in increasing the income of Lamoiko villagers, Ms. Desi Ratnasari and Mr. Ramli have empowered people who are members in the handicraft and furniture business, as seen from the income generated by members able to help to fulfill their daily lives days and increase to be greater than before becoming a member of handicrafts and furniture. The empowerment strategy undertaken by Ms. Desi and Mr. Ramli is to provide assistance by providing motivation, cooperation, and skills. Form small groups accompanied by Mrs. Desi and Mr. Ramli.